To solve the equation \(-2(-2x + 3) = 4x - 6\), we will follow these steps:
-
Distribute \(-2\) on the left side: \[ -2(-2x) + (-2)(3) = 4x - 6 \] \[ 4x - 6 = 4x - 6 \]
-
Simplify both sides: The equation simplifies to: \[ 4x - 6 = 4x - 6 \]
-
Rearranging the equation: We subtract \(4x\) from both sides: \[ 4x - 6 - 4x = 4x - 6 - 4x \] This gives: \[ -6 = -6 \]
-
Conclusion: Since both sides are equal, this means the equation is true for all values of \(x\). Thus, the solution is: \[ \text{All real numbers } x. \]
So the final answer is that \(x\) can be any real number.